2023
DOI: 10.2337/dc23-0173
|View full text |Cite
|
Sign up to set email alerts
|

At-Home Use of a Pregnancy-Specific Zone-MPC Closed-Loop System for Pregnancies Complicated by Type 1 Diabetes: A Single-Arm, Observational Multicenter Study

Abstract: OBJECTIVE There are no commercially available hybrid closed-loop insulin delivery systems customized to achieve pregnancy-specific glucose targets in the U.S. This study aimed to evaluate the feasibility and performance of at-home use of a zone model predictive controller–based closed-loop insulin delivery system customized for pregnancies complicated by type 1 diabetes (CLC-P). RESEARCH DESIGN AND METHODS Pregnant women with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We excluded inappropriate publication types, animal experiments, and unrelated research topics and then identified six studies on APS use among pregnant women with T1DM for eligibility. Upon full‐text assessment, two non‐RCTs 29,30 were excluded, and a total of four RCTs 25–28 were ultimately included. The PRISMA flow diagram is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded inappropriate publication types, animal experiments, and unrelated research topics and then identified six studies on APS use among pregnant women with T1DM for eligibility. Upon full‐text assessment, two non‐RCTs 29,30 were excluded, and a total of four RCTs 25–28 were ultimately included. The PRISMA flow diagram is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, most studies on APS use in pregnant women with T1DM have been case reports, 12–24 with only a few available randomized controlled trials (RCTs) 25–28 and non‐RCTs that have small sample sizes 29,30 . We conducted the present meta‐analysis of the few RCTs to assess the efficacy of APS use among pregnant women with T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 36% of that study population reached the HbA1c targets of <6.5% in the 1st trimester and 70% reached the target in the 2nd and 3rd trimesters despite the use of CGM. To achieve glycemic targets and lower the risk of diabetes-related complications during pregnancy in patients with type 1 diabetes, other advanced technology, such as automated insulin delivery systems, needs to be combined [ 30 , 31 ]. Ongoing studies such as automated insulin delivery amongst pregnant women with type 1 diabetes (AiDAPT) [ 32 ], and closed-loop insulin delivery in type 1 diabetes pregnancies (CIRCUIT, NCT04902378) are expected to demonstrate the advantages of a closed-loop system in pregnancy.…”
Section: Glycemic and Perinatal Outcomes With Cgm Use During Pregnancymentioning
confidence: 99%